(3aGFOI aj JMQje GdONGfs - (3SdjeGf GdGhOGQj, CHh GdQHjYs
(3ChdgG (B:s
(3CMeO Gddg JYGdi GdOhdI GdYKeGfjI s
(3BNQgG (B:s
(3eMeO Hf SYO GdOjf s
(3Vef eLehY , JQJjHgG (B: (3GdKGfis
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3CUhd Gdabgs